Observaţii asupra cărţilor de mărturie sub maledicţie arhierească în Ţara Românească - Laura Bădescu (Revista de Istorie și Teorie Literară)
The books of testimony covered by this article fall into the category of juridical documents written as a result of the issue of curse books, as had become the custom of the time. Analysis of the two categories of documents, i.e., curse books and books of testimony, offers data regarding a normative mechanism validated equally by the ecclesiastical and the lay authorities in eighteenth century Romania. The ritual of testifying under a bishop’s malediction emphasises not only certain practices specific to common law, but also elements having contributed to a pattern of thinking and expression of religious sentiment at both official and extra-ecclesiastical levels. This study draws on a corpus of texts comprising curse books and books of testimony held by the Bucharest Metropolitan Church and the Romanian National Archives, as well as documents cited in other volumes on this topic. Conclusions have been formulated, based on analysis of this corpus, regarding the entire process of registering the testimony given under curse, formalised through specific paraphenalia, acts and gestures, choosing witnesses, and taking the oath prior to the court testimony itself. Through this analysis, we seek to partially reconstruct the mechanisms behind the pre-modern legislative system, attesting not only to national acceptance of the Christian truth and the ecumenical tradition, but also to the complex links between church and laity.